2007
DOI: 10.1016/j.bbr.2007.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone influences the consummatory processes that govern ethanol drinking in C57BL/6J mice

Abstract: Although systemic allopregnanolone (ALLO; a positive modulator of GABA A receptors) has been shown to enhance ethanol-reinforced responding and to modulate drinking patterns in rodents, the effects of centrally administered ALLO on ethanol intake are not known. The current work examined the effects of intracranial ALLO on operant ethanol self-administration in food-and water-satiated mice, with a procedure designed to estimate ALLO's influence on appetitive versus consummatory processes. Male C57BL/6J (B6) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
57
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 47 publications
11
57
1
Order By: Relevance
“…Results from the control conditions also agree with previous findings showing that ALLO did not decrease locomotor activity (Beauchamp et al 2000;Ford et al 2007) or responding maintained by sucrose (Sinnott et al 2002;Janak and Gill 2003). That ALLO significantly decreased cocaine-seeking behavior in females but not in males is consistent with results from a clinical study examining the influence of PROG on the attenuation of positive subjective ratings of cocaine in cocaine users (Evans and Foltin 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Results from the control conditions also agree with previous findings showing that ALLO did not decrease locomotor activity (Beauchamp et al 2000;Ford et al 2007) or responding maintained by sucrose (Sinnott et al 2002;Janak and Gill 2003). That ALLO significantly decreased cocaine-seeking behavior in females but not in males is consistent with results from a clinical study examining the influence of PROG on the attenuation of positive subjective ratings of cocaine in cocaine users (Evans and Foltin 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Ethanol's ability to change local cellular levels of 3a,5a-THP in the NAc and CeA is particularly interesting, as these regions are strongly associated with ethanol reinforcement and consumption (Gonzales et al, 2004;McBride, 2002), and exogenous 3a,5a-THP has been shown to modulate ethanol self-administration. For example, several studies have shown that 3a,5a-THP alters ethanol consumption (Ford et al, 2007;Ford et al, 2005;Morrow et al, 2001) and reinforcement (Janak and Michael Gill, 2003;Janak et al, 1998). Ethanol-induced reductions of cellular 3a,5a-THP would most likely decrease GABA A receptor-mediated inhibition, which may alter activity of mesolimbic neurons and CeA circuitry involved in ethanol reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that sexually dimorphic effects have been noted in the interaction of ethanol and neurosteroids. ALLO pretreatment significantly increases voluntary ethanol consumption in male but not female mice (Sinnott et al, 2002) and intra-cranial injection of ALLO modulates the onset and maintenance of ethanol selfadministration but does not affect appetitive (ethanol seeking behaviors) (Ford et al, 2007).…”
Section: Ethanol and Neurosteroidsmentioning
confidence: 99%